The Response of Node and Leaf Explant of Binahong (Anredera cordifolia L.) on MS Media with Variation of BAP Concentration - Triastuti Rahayu; Ucik Mardini (Universitas Sebelas Maret, 2015)
The purpose of this study was to determine the response of nodal explants and leaves of plants binahong on MS medium with the addition of 2,4-D with BAP variation. Research was designed using two factors: factor 1: types of explants (E1 = node, E2 = leaf), factor 2: the concentration of plant growth regulator BAP (B0 = 2,4-D 2 mg / L (without BAP); B1 = 2, 4-D 2 mg / L and BAP 1 mg / L; B2 = 2,4-D 2 mg / L and BAP 2 mg / L). Explants nodes and leaves of plants Binahong sterilized using Bayclin 45